HADITH NABI SEBAGAI SUMBER AJARAN ISLAM: Dari Makna Lokal-Temporal Menuju Makna Universal - Abdul Haris (Universitas Islam Negeri Mataram, 2013)
This article discusses two existing different, contradicting views of Muslims about Hadith and offers a solution for this. The first view maintains that Hadith may contain local or temporal meanings that reflected the life of the Prophet in the seventh century of Arabia. In this view, Hadith should be seen as a historical narrative that waist closely related to its contexts. The second view holds that Hadith is the second source of Islam after the Qur’an and has become the religious reference for Muslims since early time of Islam until today, even up to the end of day. This article proves that both views are valid. It, however, proposes to find a method to understand best Hadith in contemporary Muslim’s lives. By contextualizing Hadith from its temporal meaning to its universal meaning, Hadith will be always meaningful for Muslim’s contemporary lives.